1992
DOI: 10.1021/bi00160a038
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the human stromelysin catalytic domain expressed in Escherichia coli

Abstract: Human stromelysin is a member of the matrix metalloproteinase family involved in connective tissue degradation. The stromelysin catalytic domain (SCD) lacking both propeptide and C-terminal fragment was expressed in Escherichia coli in soluble and insoluble forms. The insoluble SCD was refolded to the active form in high yield. The protein showed remarkable thermal stability and was able to cleave a thiopeptolide substrate and its natural substrate proteoglycan. The stable and active 20-kDa protein provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…It was decided to study stromelysin at pH 7, in the presence of 20-fold excess of CaCI, to avoid the [local] unfolding. Stromelysin activity is just a factor of two lower than optimum at pH 7 (Ye et al, 1992). We speculate that the unfolding at pH 6.0 occurs in the Ca2+ binding site regions because CaZ+ affinity is known to decrease 10-fold with a pH change from 7 to 5.5 (Wilhelm et at., 1993).…”
Section: Role Of Metalmentioning
confidence: 77%
See 2 more Smart Citations
“…It was decided to study stromelysin at pH 7, in the presence of 20-fold excess of CaCI, to avoid the [local] unfolding. Stromelysin activity is just a factor of two lower than optimum at pH 7 (Ye et al, 1992). We speculate that the unfolding at pH 6.0 occurs in the Ca2+ binding site regions because CaZ+ affinity is known to decrease 10-fold with a pH change from 7 to 5.5 (Wilhelm et at., 1993).…”
Section: Role Of Metalmentioning
confidence: 77%
“…As stromelysin catalytic domain is most active at pH 6.0 (Ye et al, 1992), a logical choice would be to study the molecule at or near that pH, similar to the work reported by Gooley et at. (1994).…”
Section: Role Of Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrilysin (PUMP; MMP-7) naturally lacks the C-terminal hemopexinlike domain and is an active enzyme [24]. Stromelysin and 72-kDa type IV collagenase are active with this domain removed [25][26][27]. On the other hand, fibroblast and neutrophil collagenases lacking the C-terminal domain lose the degradative activity against collagens [28,29].…”
Section: Expression and Characterization Of Rat 92-kda Type IV Collagmentioning
confidence: 99%
“…Truncated forms of the proenzymes lacking the C-terminal domain have been constructed by using DNA technology and these are the forms that were used to determine the published structures. Some kinetic studies have been performed on these domain deletion mutants and they have been shown to have catalytic and specificity characteristics similar to those of their full-length counterparts [12,13]. As part of a study designed to characterise more fully the full-length and short form enzymes, we have compared the zinc content of full-length prostromelysin-1 and progelatinase A with that of the truncated mutants, N-prostromelysin-1 and N-progelatinase A.…”
Section: Introductionmentioning
confidence: 99%